Avaliação multicritério de desempenho do setor público: uma proposta para apoiar a gestão do trabalho remoto em um órgão público - Marcon, Gabriela Almeira (2017)
People organize in society because of the advantages of the collective. Organizations come from the congregation of plural interests. It is from this point of view that the concept of Public Administration emerges. The evolution of information and communication technologies has increasingly allowed the transformation of public management. The efficiency in the public sector, besides the managerial aspect, is a principle of constitutional stature. The use of computerized systems by the government has enabled, above all, changes in labor relations. A new policy that allows working outside the conventional environment innovates in the way responsibilities are organized in the public sector. Teleworking allows public servants to make better use of their potential, better manage their time, while remaining in alignment with the strategies, values and objectives of the organization to which they relate. The evaluation of performance in the public sector went through different phases and stood out from the studies on the New Public Management, which suggests the adoption of private sector practices in the public sphere. A tangential point between public and private administration is the adoption of performance appraisal systems as a management practice. The question that guided this research was: What criteria should be considered in the construction of a model of evaluation of the performance of the remote labor systematics of the Federal Attorney's Office in Santa Catarina? The aim of this study - which was to build a performance evaluation model to support the management of remote work adopted at the Federal Attorney's Office in Santa Catarina, based on the Multicriteria Decision Aid – Constructivist Methodology (MCDA-C) - was reached from the each of the specific goals proposed. The methodological approach is quanti-qualitative; inductive and constructivist (regarding its philosophy). Regarding the nature of the objectives, the research is exploratory and descriptive. It was also cross-sectional. The investigative strategies were case study, bibliographical, documentary and participant research. As for the data collected, they were primary and secondary. This study made it possible to explain that management models in Brazil were not replaced over the years, observing the coexistence of aspects, above all, of bureaucracy and managerialism. The Proknow-C intervention tool made it possible to organize a fragment of the literature representative of the Performance Evaluation of the Public Sector and to broaden the researcher's knowledge about the subject. The construction of the model from the MCDA-C enabled the contemplation of several aspects considered relevant by the actors involved in the decision process, in the decision maker's perception, so that the potential actions could be evaluated according to a set of criteria. From this performance evaluation model, with 38 performance indicators, the decision maker was able to expand his knowledge about the context, looking for deficiencies and potentialities in management. It goes on to a mechanism for monitoring and improving telecommuting, reflecting its concerns in a comprehensive and detailed manner. It is noted that the completion of the entire MCDA-C evaluation phase was not the subject of the study, according to the delimitation.